RESPONSE OF OLIVE TREE CULTIVARS TO DIFFERENT LEVELS OF NUTRIENT STRESS - Naija, Dhouha Saidana; Boussadia, Olfa; Dhiab, Ali Ben; Mariem, Fathi Ben; Ghariani, Wafa; Braham, Mohamed (European Scientific Journal, ESJ, 2014)
To evaluate the response of the olive tree cultivars Meski and Chetoui to nutrient stress, a complete privation of major nutrients such as nitrogen (N), phosphorus (P), magnesium (Mg), and potassium (K) was chosen. Mineral composition, vegetative development, starch accumulation and their evolutions and distributions in the different compartment of the tree were studied. The survey of mineral diagnosis showed significant modification of the tree mineral alimentation, as well as cationic and anionic at varying degrees. Synergistic and antagonistic actions of the mineral elements were registered, reinforced by the imposed nutrient stress. The distribution of dry matter in the various organs of the olive tree cultivars was affected. The removal of nitrogen seemed to favor the allocation of carbon from leaves to roots. The effect of phosphorus deprivation was marked particularly on the development of the root system which seemed to be small, sparse and poorly developed. Important starch synthesis and storage was also revealed following nitrogen deficiency, but it was very weak after the suppression of magnesium, which may provoke a weakening of growth and development of these young olive trees. Cultivar comparison showed the superiority of Chetoui to support the severe imposed nutrient stresses.